Augmented lipid accumulation in ethyl methyl sulphonate mutants of oleaginous microalga for biodiesel production. (October 2017) - Mehtani, Juhi; Arora, Neha; Patel, Alok; Jain, Priyanka; Pruthi, Parul A.; Poluri, Kirshna Mohan; Pruthi, Vikas
Graphical abstract: Highlights: High lipid accumulating mutants of C. minutissima using ethyl methyl sulphonate. Mutants exhibited enhanced growth rate and photosynthetic pigments. Reduced starch content indicated re-allocation of carbon flux to lipids. Increased MUFA and decreased SFA/PUFA content in mutant CM7. High MUFA improves shelf life, cold flow properties and cetane number of biodiesel. Abstract: The aim of this work was to generate high lipid accumulating mutants of Chlorella minutissima (CM) using ethyl methyl sulphonate (EMS) as a random chemical mutagen. Amid the 5% surviving cells after exposure to EMS (2 M), three fast growing mutants (CM2, CM5, CM7) were selected and compared with wild type for lipid productivity and biochemical composition. Among these mutants, CM7 showed the maximum biomass (2.4 g/L) and lipid content (42%) as compared to wild type (1.5 g/L; 27%). Further, the mutant showed high photosynthetic pigments with low starch content signifying the re-allocation of carbon flux to lipid. The obtained mutant showed no visible morphological changes in comparison to its WT. The fatty acid profile showed increase in monounsaturated fatty acids while decreased saturated and polyunsaturated fatty acids signifying good quality biodiesel. The mutant strain thus obtained can be optimized further and applied for enhanced biodiesel production.